Cyclotron resonance conditions in current-carrying plasmas - Grishanov, N.I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2018)
The resonant cyclotron wave-particle interactions in the cylindrical current-carrying plasma and axisymmetric toroidal plasma models for large aspect ratio tokamaks with circular, elliptic and D-shaped cross-sections of the magnetic surfaces have been analyzed. The corresponding conditions are derived by solving the linearized Vlasov equations for perturbed distribution functions of plasma particles, accounting for the geometry of a confinement magnetic field in the zero-order over magnetization parameters. It is shown that the Doppler shift at the cyclotron resonance conditions in the current-carrying plasmas is entirely different from ones in uniform magnetic field.